PRE-ROMAN DACIAN SOCIETY IN ROMANIAN HISTORIOGRAPHY - Alexandra NICOLESCU (Journal of Ancient History and Archaeology)
Abstract: This work aims to reconstruct the itinerary of the Romanian historiography that targets the Dacian society from the Dacian royal period. The study follows the evolutionary direction of the opinions regarding the indigenous society in Dacia and its stratification was followed. In the Romanian historiography, six periods are highlighted: the period of the first scientific historiography (the second half of the 19th century-1918), the interwar period(1919-1948), the Stalinist period(1948-1964), the period of the return to national values(1964-1975), the era of nationalist communism(1975-1989) and the climate of freedom after 1989. In an analytical and objective manner, the opinions outlined and stated by historians in each historiographic period are rendered. Great attention was paid to historical writing and to the conceptions set forth by historians regarding the stratification of the Dacian society, these being determined by the structure of the present. Keywords: Romanian historiography, the Dacian society, pileati, comati.